Adaptation of online training in UiTM during Covid-19 pandemic: experience of ILD UiTM / Mohd Rafizi Rahmad and Siti Zalipah Ibrahim - Rahmad, Mohd Rafizi; Ibrahim, Siti Zalipah (Universiti Teknologi MARA, 2021)
Covid-19 pandemic has hit the world at the end of 2019 and Malaysia is one of the affected countries. The Malaysian government has tried to minimize movement to reduce the spread of this virus. As we all know, the learning and training process is one of the areas affected. All institutions of higher learning and schools had to be closed for the benefit of all. UiTM has also issued operating guidelines during Covid-19. Institute of Leadership Development (ILD) UiTM is a training centre for staff that needs to be managed and given attention. Even in uncertain situations, training for staff needs to be continued. As a solution, ILD UiTM has adopted new practices to continue the functions of this centre. Online training was introduced to further enliven the training to staff. But there are challenges in reaching, adapting, and achieving effectiveness of online training.